2022
DOI: 10.1007/s00464-022-09200-2
|View full text |Cite
|
Sign up to set email alerts
|

Reconstructing topography and extent of injury to the superior mesenteric artery plexus in right colectomy with extended D3 mesenterectomy: a composite multimodal 3-dimensional analysis

Abstract: Background Superior mesenteric artery plexus (SMAP) injury is reported to cause postoperative intractable diarrhea after pancreatic/colonic surgery with extended lymphadenectomy. This study aims to describe the SMAP microanatomy and extent of injury after right colectomy with extended D3 mesenterectomy for cancer. Methods Three groups (I) anatomical dissection, (II) postmortem histology, and (III) surgical specimen histology were included. Nerve count and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 41 publications
2
7
0
Order By: Relevance
“…In addition, they showed that two main nerve cords (one traveling ventrally and other traveling dorsally) are present along the SMA with an anti-clockwise rotation in a helical manner. We are gratified to note that these results concur with our recent results [2], confirming the hypothesis of a nonlinear course of this plexus, namely a helical trajectory of the nerves around the SMA.…”
Section: Dear Editorsupporting
confidence: 91%
“…In addition, they showed that two main nerve cords (one traveling ventrally and other traveling dorsally) are present along the SMA with an anti-clockwise rotation in a helical manner. We are gratified to note that these results concur with our recent results [2], confirming the hypothesis of a nonlinear course of this plexus, namely a helical trajectory of the nerves around the SMA.…”
Section: Dear Editorsupporting
confidence: 91%
“…In our procedure, the extent of injury to the superior mesenteric nerve plexus is 48% of the area. 2 A study 3 has shown that the effect of such injury to the nerve plexus on the patient's bowel function is comparable to that of patients who have undergone traditional D2 mesenterectomy.…”
Section: With Great Interestmentioning
confidence: 99%
“…The more and more accepted complete mesocolic excision with D3 lymphadenectomy for cancer [ 4 , 5 ], either by open access, laparoscopy or robotic surgery has shed new light on the lymphatic anatomy of the mesentery of the small and the large bowel. The D3 volume has been defined according to the landmarks of the superior mesenteric vein (SMV) and artery (SMA) and their principal affluents/branches [ 6 , 7 ]. The limits are as follows: 2 cm-distal to the origin of the ileocolic artery and cranial to the origin of the middle colic artery (MCA), 3 cm right to the right border of the SMV, and the left border of the SMA.…”
Section: Introductionmentioning
confidence: 99%
“…This volume includes the tissue in front and behind the mesenteric vessels, with the posterior limit of the fusion fascias of Treitz and Toldt. It is well known that the lymphatic plexuses are found here in the superficial submesothelial space and the deeper lymphovascular bundles within the mesenteric connective tissue lattice [ 6 , 7 , 8 ]. From the mesenteric collecting lymphatics, the lymph is carried to the central/preterminal superior mesenteric nodes around the corresponding artery [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation